How does renewable energy consumption affect economic growth in the traditional and new member states of the European Union?. (November 2020) - Smolović, Julija Cerović; Muhadinović, Milica; Radonjić, Milena; Đurašković, Jovan
Abstract: The aim of this paper is to examine the relationship between renewable energy consumption and economic growth in both traditional and new EU member states over the period from 2004 to 2018. In order to properly examine the relationship between the defined variables, we used a Pooled Mean Group (PMG) estimator in a dynamic panel setting (an ARDL model). The obtained results show that the impact of renewable energy consumption on economic growth is positive and statistically significant in the long run in both samples of countries. In the short term, the impact of renewable energy consumption on economic activity proved to be negative in new member states, while in traditional member states it had no statistically significant impact. These results suggest significant implications for economic policy makers.